PENGARUH TUJUH KONTAK KONSELING LAKTASI TERHADAP KEJADIAN POSTPARTUMBLUES - Yanik Muyassaroh; Komariyah Komariyah; Aulia Fatmayanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Postpartum blues is an early onset mental disorders on postpartum mothers, who could be bad on the mother and her baby. This situation usually arises between the three to ten post childbirth, often after the patients out of the hospital. One of the factors causing postpartum blues i.e. difficulty breast-feeding, which can increase the risk of depression. A variety of therapies that can be used to reduce the incidence of depression post, on the mother, one of them with counseling.Analyse the influence sevencontact of lactation counselling against postpartum blues.The design of this research uses quasi eksperiment with nonrandom control group design. The number of samples 20responden, each group of 10 respondents. Data analysis using mann whitney.There was a difference in the control group and treatment group with p value : 0000There are influence of seven contacts lactation counseling against postpartum blues.